2013
DOI: 10.2176/nmc.53.474
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Neuroimaging Findings in 12 Cases of Recurrent Glioblastoma With Communicating Hydrocephalus

Abstract: Clinically, recurrent glioblastoma multiforme (GBM) is often associated with communicating hydrocephalus. We hypothesized that there are specific magnetic resonance (MR) imaging findings at the diagnosis of recurrent GBM that predict subsequent hydrocephalus. Various clinical characteristics were investigated including outcome and MR imaging findings in 12 patients with recurrent GBM followed by hydrocephalus (Hydro group) and 21 patients with recurrent GBM without hydrocephalus (Non-hydro group). Patient age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…RPA is considered to be a machine learning method and usually requires a large sample to establish a classification model from a training data and verify this model by another test sample. RPA can be realized through computer and many medical care studies have used RPA to detect prognostic and risk factors ( 19 , 20 ), as well as diagnosis in imaging study ( 21 ). Classification and regression tree (CRT) analysis is a kind of tree-building technique from RPA to the generation of clinical decision rules ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…RPA is considered to be a machine learning method and usually requires a large sample to establish a classification model from a training data and verify this model by another test sample. RPA can be realized through computer and many medical care studies have used RPA to detect prognostic and risk factors ( 19 , 20 ), as well as diagnosis in imaging study ( 21 ). Classification and regression tree (CRT) analysis is a kind of tree-building technique from RPA to the generation of clinical decision rules ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Onuma et al reported that median survival in GBM patients with LMD is longer in patients without communicating hydrocephalus [38]. Treatment of hydrocephalus with VP or lumboperitoneal shunt in patients with LMD has been shown to improve survival [39].…”
Section: Surgical Treatment Of Lmd In Gbm Hydrocephalus Vp Shuntmentioning
confidence: 99%
“…Patients with LMS can suffer from cranial nerve palsies, increased intracranial pressure syndrome, hydrocephalus, meningism, and/or focal neurological deficits [1, 7, 15, 20, 33, 71–76]. Seizure frequency does not seem to increase during LMS development [77].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Of note, although LMS may manifest as communicating hydrocephalus [33], only 25%–40% of patients with LMS present this complication [75, 91].…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation